Setting the Structural Reform of Supply-Side as the Focus and Shifting the Economic Development Model - Yang Jiayi; Li Jiaxiang (Contemporary Social Sciences, 2017)
To focus on SRSS during the 13th Five-Year Plan period (2016-2020) is a necessary response to the changes of the international economic environment and to China’s goal of achieving the new normal in economic development. The main reason why the focus shifts from changing EDM to reforming the supply-side structure lies in the fact that structural reform boosts the transformation of EDM, and only by accomplishing the former will the latter be realized. Today SRSS is faced with challenges like different ideologies, insufficient conditions and backward regulations. It should be led by the Five Major Development Concepts proposed by President Xi Jinping, “Innovation, coordination, greenness, openness and sharing,” and the “supply-side” and “demand-side” must be simultaneously propelled.